DETERMINATION OF OPTIMAL TRAINING LOAD PARAMETERS OF FOOTBALL SESSIONS IN THE PHYSICAL TRAINING SYSTEM OF CADETS (World Bulletin of Physical Education and Sports Science, 2026)
The physical training system of cadets in military and law enforcement educational institutions must ensure a high level of physical fitness, functional readiness, and adaptive capacity. Traditional training methods, while effective, often lack variability and motivation. Football-based training has gained attention as a multifunctional physical activity; however, scientifically substantiated training load parameters adapted to cadets remain insufficiently studied.
Keywords: Cadets; Physical training system; Football-based training; Training load optimization; Functional readiness; Heart rate monitoring; Physical fitness.